Perencanaan Infrastruktur Riau: Mewujudkan Visi Riau 2020 - Ikhsan, Muhammad (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2003)
Several backgrounds of infrastructure condition in Riau including geography, existing infrastructure and the people's condition will be presented in this paper.